2013
DOI: 10.2174/09298665113206660095
|View full text |Cite
|
Sign up to set email alerts
|

Core Functional Sequence of C-terminal GAG-binding Domain Directs Cellular Uptake of IGFBP-3-derived Peptides

Abstract: The current study clarifies the role of the Glycosaminoglycan (GAG)-binding domain of insulin-like growth factor binding protein-3 (IGFBP-3) in cell penetration. The cell penetration function of IGFBP-3 has been mapped to an 18-residue GAG-binding domain in the C-terminal region that mobilizes cellular uptake and nuclear localization of unrelated proteins. Uptake of KW-22, a 22-residue peptide that encompasses the 18-residue GAG-binding domain, and another IGFBP-3 peptide carrying a streptavidin protein cargo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Mutants of GAGs possessing defects in truncation of GAG could affect the cellular uptake of IGFBP-3 ranging from impaired cellular uptake to complete inability to internalize (Liu et al, 2014). In the same study, Liu et al (2014) demonstrated that IGFBP-3 peptides entered as a CPP in a GAG-dependent manner. An 18-mer peptide including the GAG domain of the C-terminus was synthesized and of these, 8-mer peptides retained a stronger binding to GAGs, whereas 10-mer peptides retained most of the cellular uptake functions.…”
Section: Gag Domain Of Igfbp-3 Required For Cell Penetration Peptide mentioning
confidence: 89%
See 4 more Smart Citations
“…Mutants of GAGs possessing defects in truncation of GAG could affect the cellular uptake of IGFBP-3 ranging from impaired cellular uptake to complete inability to internalize (Liu et al, 2014). In the same study, Liu et al (2014) demonstrated that IGFBP-3 peptides entered as a CPP in a GAG-dependent manner. An 18-mer peptide including the GAG domain of the C-terminus was synthesized and of these, 8-mer peptides retained a stronger binding to GAGs, whereas 10-mer peptides retained most of the cellular uptake functions.…”
Section: Gag Domain Of Igfbp-3 Required For Cell Penetration Peptide mentioning
confidence: 89%
“…domain (Lee et al, 2004), heparin binding domain or GAG binding domain (Smith et al, 1994;Fowlkes and Serra, 1996;Liu et al, 2014), metal binding domain (Singh et al, 2004), and ALS binding domain (Firth et al, 1998b), vide supra Figure 1. Therefore, the C-terminal domain of IGFBP-3 plays an important role in metal binding, cellular uptake, as well as nuclear localization of the protein.…”
Section: The Structure Of Igfbp-3mentioning
confidence: 99%
See 3 more Smart Citations